2020
DOI: 10.1097/md.0000000000022781
|View full text |Cite
|
Sign up to set email alerts
|

In situ buccal carcinoma in a teenager after hematopoietic stem cell transplantation

Abstract: Rationale: Hematopoietic stem cell transplantation (HSCT) is the most effective treatment for the majority of patients who have malignant haemolytic disease. Although the success rate of HSCT has increased, the increasing number of cases suffering from secondary solid malignancies after HSCT has attracted more interest recently. Patient concerns: A 16-year-old female patient from China presented with a crusty and painful lesion on the left buccal mucosa with a history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…It has been reported that some patients develop OSCC from oral lichenoid lesions caused by chronic graft-versus-host disease after hematopoietic stem cell transplantation in the treatment of hematopoietic malignancies [ 69 , 70 ]. As a hypothesis to explain these cases, Hasegawa et al in our research group proposed that bone marrow (BM)-derived stem cells could be the origin that causes the development of OSCC [ 43 ].…”
Section: Possible Candidates Of the Origin Of Cscs In Osccmentioning
confidence: 99%
“…It has been reported that some patients develop OSCC from oral lichenoid lesions caused by chronic graft-versus-host disease after hematopoietic stem cell transplantation in the treatment of hematopoietic malignancies [ 69 , 70 ]. As a hypothesis to explain these cases, Hasegawa et al in our research group proposed that bone marrow (BM)-derived stem cells could be the origin that causes the development of OSCC [ 43 ].…”
Section: Possible Candidates Of the Origin Of Cscs In Osccmentioning
confidence: 99%
“…Hematopoietic stem cell transplantation (HSCT) represents an effective procedure, widely used as a therapeutic treatment for patients diagnosed with various malignant haematological disorders, bone marrow failure disease, and congenital immune deficiencies [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hematological malignancies and lymphoproliferative diseases are relatively common and usually present early after the HSCT [ 6 ]; solid cancers (involving the skin, oral cavity, genitourinary tract, breast, bone, connective tissue, brain, liver, lung, and thyroid) are less frequent with an incidence rate of 2 to 6% at 10–15 years after HSCT and account for approximately 5% to 10% of late death in patients after HSCT [ 1 , 2 ]. The risk of secondary solid tumors begins to increase around 10 years after transplantation and continues even 20 years later [ 1 ]. In fact, the cumulative incidence of secondary solid malignancies is 2.5% (95% CI: 2.0–3.0%) at 10 years, 5.8% (95% CI: 4.3–7.0%) at 15 years, and 8.8% (95% CI: 6.2–12.3%) at 20 years after HSCT, respectively [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations